2018
DOI: 10.1007/s10637-018-0592-y
|View full text |Cite
|
Sign up to set email alerts
|

Acquired resistance to an epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) in an uncommon G719S EGFR mutation

Abstract: Background Acquired resistance (AR) to an epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) is a common event, and several underlying mechanisms, including T790 M, MET amplification and PTEN downregulation, have been reported for the common EGFR mutations. EGFR G719X is an uncommon mutation that has been reported to show sensitivity to EGFR-TKIs. However, no established cell lines harboring the EGFR G719X have been reported in the literature. Materials and Methods G719S-GR cells were establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“… 34 However, the mechanism of acquired resistance for uncommon mutations remains unclear. 35 , 36 A multicenter study has shown that acquired T790M mutation was common in patients with NSCLC with icotinib‐resistant EGFR uncommon mutations. Other several resistance mechanisms to icotinib in NSCLC harboring uncommon mutations include EGFR extracellular domain mutation, BCL2L11 loss, MET amplification, ERBB2 amplification, MYC amplification, PTEN mutation, and PIK3CA mutation.…”
Section: Discussionmentioning
confidence: 99%
“… 34 However, the mechanism of acquired resistance for uncommon mutations remains unclear. 35 , 36 A multicenter study has shown that acquired T790M mutation was common in patients with NSCLC with icotinib‐resistant EGFR uncommon mutations. Other several resistance mechanisms to icotinib in NSCLC harboring uncommon mutations include EGFR extracellular domain mutation, BCL2L11 loss, MET amplification, ERBB2 amplification, MYC amplification, PTEN mutation, and PIK3CA mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of those mutations increased from the colitis to nally the CRC, so they could be used as predictors for disease progression. Most of the above identi ed somatic mutations were observed mostly with the CRC [47], except for (c.640delT in ATM), (c.1621A > C in KIT), (c.2071G > A in RET) & (c.121delG in TP53) which were observed respectively in breast [57], soft tissues [58] & head and neck cancers [59]. This is the rst study to report their association with the colorectal carcinogenesis in Egyptian CRC patients.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, simulations indicate that the distance between residues L718 and G796 is increased widening the ATP-binding site for TKIs to enter (conversely, the T790M mutation causes the distance between L718 and G796 to decrease) [60] . Moreover, the G719S mutation destabilizes the inactive conformation and promotes the active conformation of the kinase, leading to more TKI sensitivity [61] , [62] , [63] , [64] , [65] . However, when G719S is combined with T790M as a double mutation, the secondary T790M mutation overturns the impact of G719S on the distance between the P-loop and activation loop [60] .…”
Section: Resultsmentioning
confidence: 99%